Characteristics of the Social Support Networks of Maltreated Youth: Exploring the Effects of Maltreatment Experience and Foster Placement. Issue 3 (2nd December 2014) - Negriff, Sonya; James, Adam; Trickett, Penelope K.
Abstract Little is known about the social support networks of maltreated youth or how youth in foster care may compare with those who remain with their parent(s). Social network characteristics and perceived social support were examined between (1) maltreated and comparison youth, (2) maltreated youth who remained with their biological parent, those with a foster parent, or a those with a kin caregiver, and (3) youth in stable placements and those who have changed placements. Data came from a sample of 454 adolescents (241 boys, 9–13 years old at enrollment) who took part in a longitudinal study of child maltreatment. Participants completed three assessments approximately 1 year apart. Results showed that on average, maltreated adolescents named significantly fewer people in their network than comparison adolescents. At Time 2, comparison adolescents reported more same‐aged friends. In the maltreatment group, youth with a foster parent reported significantly more older friends than maltreated youth with a kin caregiver. Fewer maltreated youth named a biological parent on the social support questionnaire at all three time points. More youth in kinship care described their caregiver as supportive than those in foster care. These findings indicate that despite heterogeneous placement histories, social support networks among maltreated youth were very similar.